Oír o ver / Oír y ver. Hacia una espectacularidad comprensiva - Florence d' Artois; Héctor Ruiz Soto (Criticón, 2020)
This article proposes an approach to the Spanish theater of the Golden Age focused on its intersensorial spectacularity. After reviewing the point of view of playwrights such as Lope de Vega and Calderón de la Barca on the sensitive spectacle, the meta-theatrical dispute between sight and hearing is analyzed. We complete the oculocentric perspective by highlighting a synesthetic Spanish spectacularity, visible as much in anti-theatrical criticism as in other indirect testimonies (El pasajero, Suárez de Figueroa) and in metatheatrical fiction itself (Morales, Los naufragios de Leopoldo).